Efficiency of Non-Walrasian Equilibria - Nayak, P. R. (Econometrica, 1980)
[In this paper, Pareto efficiency properties of a non-Walrasian equilibrium for an exchange economy are analyzed. The equilibrium considered is a generalized version of Drèze's equilibrium with price rigidities and rationing.]